2005
DOI: 10.1021/la0525731
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Orientation of Enzymes on Surfaces for Ligand Screening Probed by Force Spectroscopy

Abstract: In this letter, we show that electrostatic immobilization provides a simple but effective approach for the immobilization and orientation of carbonic anhydrase onto charged surfaces. The enzyme is oriented differently on oppositely charged surfaces, with the majority of active sites facing upward on a positively charged surface and downward on a negatively charged surface. An array of negatively charged microscale surface patterns within a positively charged background was prepared by microcontact printing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…A larger population of adsorbed TLL molecules are thought to be oriented with the active site facing the surface on hydrophobic surfaces compared to hydrophilic. A similar conclusion about proteins preferring different orientations depending on the properties on the surface has been drawn with carbonic anhydrase, whose orientation on a surface is thought to depend on the surface charge due to a strong positive domain close to the active site [37].…”
Section: Discussionmentioning
confidence: 52%
“…A larger population of adsorbed TLL molecules are thought to be oriented with the active site facing the surface on hydrophobic surfaces compared to hydrophilic. A similar conclusion about proteins preferring different orientations depending on the properties on the surface has been drawn with carbonic anhydrase, whose orientation on a surface is thought to depend on the surface charge due to a strong positive domain close to the active site [37].…”
Section: Discussionmentioning
confidence: 52%
“…5,6 A part of active sites might thus be buried and inaccessible, leading to a dramatic decrease in the bioactivity compared with the native enzymes. Few attempts to control the enzymatic orientation through tailoring the wetting properties 7 or surface charges 8 of the supports revealed that the rational artificial interference was not infeasible. However, in the approaches already reported, a reactive terminal tag or a protein conjugate had to be used.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the approaches already reported, a reactive terminal tag or a protein conjugate had to be used. 7,8 Recently, efforts have been made toward the orientated attachment of proteins to solid surfaces through electrostatic assembly. [8][9][10] The electrostatic recognition strategy is thus believed to be a simple and biocompatible alternative to control the protein orientation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that an active enzyme, carbonic anhydrase (CA), can be controllably oriented on charged surfaces by electrostatic immobilization 9,10. The enzyme was found to form a complete layer on both the positively (terminated with a pyridinium salt) and negatively (terminated with a carboxylic acid) charged surfaces, however, with different orientations.…”
Section: Introductionmentioning
confidence: 99%